Development of Halloysite Nanotube As The Future Coating Inhibitor Against Corrosion - Padil, Syariza Fadli Ansary (IRC, 2021)
Almost every metal and its alloys are susceptible to corrosion attacks which will lead to a deficiency in material integrity, major functionality, and equipment failure.